The effect of working capital management on firm's profitability: evidence from Malaysia / Clstica Muin - Muin, Clstica (2017)
A well designed and implemented working capital management is expected to contribute positively to the creation of a firm’s value. Working capital management had been a focus of various researchers and companies recently as it can be guidance for financial manager in decision made can increase the value of the company. The purpose of this study is to examine the effect of working capital management on profitability of Malaysian companies. The study is based on a sample of top 30 companies listed on the Main Board of Bursa Malaysia, covering a span of ten years starting from 2007 until 2016. In order to fulfill the objective of this study, panel data was tested on quantitative basis using descriptive and regression analysis. The dependent variable, return on asset is used as a measure of profitability. Meanwhile, the key independent variables used in this analysis is Account receivables days, Account payables days, Inventories days and Cash conversion cycle. The result provides useful input to the firms in enhancing the efficiency of the companies.